2021
DOI: 10.1186/s10194-021-01291-x
|View full text |Cite
|
Sign up to set email alerts
|

Mild traumatic brain injury affects the features of migraine

Abstract: Background Headache is one of the most common symptoms after concussion, and mild traumatic brain injury (mTBI) is a risk factor for chronic migraine (CM). However, there remains a paucity of data regarding the impact of mTBI on migraine-related symptoms and clinical course. Methods Of 2161 migraine patients who participated in the American Registry for Migraine Research between February 2016 and March 2020, 1098 completed questions assessing histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 68 publications
2
11
1
Order By: Relevance
“…With regards to the prevalence of moderate to extremely severe levels of depressive symptoms in this study, there are no directly similar studies to compare outcomes. However, Lucas et al 13 reported similar results, such as, a prevalence of 15% for depression at baseline among patients with mild traumatic brain injury. Both studies employed standardized questionnaires to assess depressive symptoms.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…With regards to the prevalence of moderate to extremely severe levels of depressive symptoms in this study, there are no directly similar studies to compare outcomes. However, Lucas et al 13 reported similar results, such as, a prevalence of 15% for depression at baseline among patients with mild traumatic brain injury. Both studies employed standardized questionnaires to assess depressive symptoms.…”
Section: Discussionmentioning
confidence: 77%
“…Both studies employed standardized questionnaires to assess depressive symptoms. Lucas et al 13 operationalized depression as a score ≥10 on the Patient Health Questionnaire-9, while in this study, moderate-extreme levels of severe depressive symptoms were defined as a score ≥14 on the depressive subscale of the DASS-21. 8,9 The majority of cases in this study suffered from migraines followed by those with chronic-tension-type headaches.…”
Section: (mentioning
confidence: 97%
“…It is noted, however, that many patients with FD/MAS have an even earlier diagnosis and receive treatment shortly after yet still suffer from pain, headaches or migraine. Patient B not only had a much later FD diagnosis, but also experienced multiple concussions, which collectively may have contributed to or worsened her chronic craniofacial pain and migraine phenotype ( 27 , 28 ). Further insights into why Patient B has not experienced pain relief despite the use of multiple modes of therapy may be garnered by considering her feelings of helplessness or constant rumination of pain as defined by the pain catastrophizing scale.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] There are several prior analyses that have included ARMR data and that might have included patients in this analysis. [24][25][26][27][28][29][30]…”
Section: Study Population /Inclusion and Exclusion Criteriamentioning
confidence: 99%